Hubungan Frekuensi Konsumsi Serat Dan Lemak Dengan Status Gizi Remaja SMA - Tiara Sang Ether Asy-Shifa; Muwakhidah Muwakhidah; Farida Nur Isnaeni (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Adolescent nutrition issues are becoming an important issue in Indonesia, marked by the increasing prevalence of overnutrition and obesity due to unbalanced diets. Adolescent nutritional status is an important indicator in assessing the health and development of the younger generation. This study aims to determine the relationship between the frequency of fiber and fat consumption with the nutritional status of adolescents at SMA Negeri 4 Surakarta. This study used an observational design with a cross-sectional approach and involved 100 students in grades X and XI selected using the proportionate stratified random sampling technique. Data were collected through the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) questionnaire for fiber and fat intake and body mass index according to age (BMI/A) for nutritional status. The analysis used to determine the relationship between fiber and fat intake with nutritional status used the Pearson Product Moment test. The results showed that fiber consumption in adolescents with overnutrition status was 60% who consumed less fiber and obesity nutritional status who consumed less fiber was 33.3%. Fat consumption in adolescents with overnutrition status was 43.8% who consumed more fat and obesity nutritional status who consumed more fat was 31.2%. The nutritional status of adolescents consists of 8% undernutrition, 74% good nutrition, 10% overnutrition, and 8% obesity. Data analysis shows that there is a significant relationship between the frequency of fiber and fat consumption with nutritional status.